Analysis Of The Communication Style Of Tiktok Shop Live Streaming Hosts Based On The Aida Model Stages - Nazwa Syahda Anisa; Btari Mariska Purwaamijaya; Asep Nuryadin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The rapid growth of social commerce in Indonesia has given rise to live streaming commerce, an interactive marketing strategy that merges entertainment, communication, and real-time sales. Within this context, hosts act as cruciall role as the primary mediators between products and audiences. This study examines TikTok Shop hosts communication styles in relation to the AIDA model stages. A qualitative approach was employed using a case study of the TikTok Shop account @alamme.official, a brand specializing in healthy food products. Data were collected through audio-visual content observation, semi-structured interviews, and key data metrics. The audio-visual observation data were analyzed using the Reflexive Content Analysis (RCA) technique, while the interview and performance data were utilized to provide contextual and complementary insights for interpreting the results. The findings reveal three distinct communication style patterns which interaction-oriented with emotive characteristics (Host A), task-oriented with emotive characteristics (Host B), and a combination of task-oriented with supportive characteristics (Host C). Among these, the task-oriented and supportive communication style was most successful in optimizing all stages of the AIDA model, as reflected in the highest levels of audience interaction, product clicks, and transactions compared to other communication styles identified in this study. Base on findings, this study conclude that a warm, empathetic, and responsive communication style contributes significantly to enhancing marketing communication effectiveness within the live streaming commerce. This research contributes for developing effective live streaming commerce style communication and recommends further analysis to assess the scalability of task-oriented and supportive interactions across diverse live commerce environments.